In every classroom: the report of the president's select comittee for lesbian and gay concerns - Anderson, James D.; Nieberding, Ronald A. (New Brunswick: Rutgers, 1989)
"James D. Anderson (chairperson) ; Ronald A. Nieberding (ed.) Fonds Suzan Daniel (FSD)"